Persepsi Pelaku UMKM Terhadap Kewajiban Pajak - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This qualitative study explores how micro, small, and medium enterprise (MSME) actors perceive tax obligations within the Indonesian fiscal environment. The research aims to understand the attitudes, awareness levels, and behavioral tendencies of MSME actors toward taxation. Using a phenomenological approach, data were collected through semi‑structured interviews with MSME owners from various sectors. Findings indicate that perceptions are shaped mainly by three factors: clarity of tax regulations, administrative complexity, and perceived benefits of paying taxes. While most respondents acknowledge the importance of taxation for national development, challenges such as limited knowledge, fear of audits, and difficulties in using digital tax systems persist. The study suggests that targeted education programs and simplified procedures could strengthen voluntary compliance.